Elastic Band Causing Exfoliation of the Upper Permanent Central Incisors - Monica Ghislaine Oliveira Alves; Dárcio Kitakawa; Joao Batista Macedo Becker; Adriana Aigotti Haberbeck Brandão; Luiz Antonio Guimarães Cabral; Janete Dias Almeida (Hindawi Limited, 2015)
Objective. This study reports a case in which elastic band use culminated in the loss of the incisors. Case Report. An 11-year-old white girl was seen complaining of pain, with purulent discharge and severe tooth mobility. The bone destruction detected radiographically in the region, despite its single location and absence in posterior quadrants of the maxilla and/or mandible, was similar to that observed in Langerhans cell disease. To our surprise, an elastic band involving the midportion of the roots of the two upper central incisors was found during biopsy. The debris was removed and a metal wire was placed in permanent maxillary right and left incisors. The patient was followed up, but no improvement in tooth mobility was observed. Bone loss increased, and internal resorption and root exposure occurred, which culminated in the extraction of permanent maxillary right and left incisors. Conclusion. The present case highlights the fact that professionals sometimes are confronted by anamnestic reports never seen before.